Development of acrylic‐based powder coatings with incorporation of montmorillonite clays. Issue 27 (13th March 2017) - Catarina, Gilmar Antônio Santa; Borsoi, Cleide; Romanzini, Daiane; Piazza, Diego; Kunst, Sandra Raquel; Scienza, Lisete Cristine; Zattera, Ademir José
ABSTRACT: Powder coatings have been receiving attention because they are environmentally friendly. They do not contain solvents in their composition, and their components have decorative and corrosion‐protection functions, among many others. However, the presence of polymers in their composition increases the risk of combustion in adverse situations. In this context, this study aims to develop and characterize acrylic‐based powder paints with the addition of 2 wt % and 4 wt % montmorillonite clays (MMT) as Cloisite 30B (MMT‐30B) and Cloisite 15A (MTT‐15A), employed as flame retardants. The characterization of the coatings was carried out by thermogravimetric analysis (TGA), X‐ray diffraction, and scanning electron microscopy. After application of the coatings on carbon steel substrates, flammability tests were performed. The coatings with 2 wt % MMT‐30B showed overall better results, especially in the flammability tests. Flames spread less on these coatings than on the other systems. However, when the surface and bottom temperatures were analyzed by the cone calorimeter test, the samples prepared with 4 wt % MMT‐15A were considered safer to be applied in fire scenarios. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45031. Abstract :